On the Role of Personality Traits in Followee Recommendation Algorithms - Tommasel, Antonela (2015)
Followee recommendation is a problem rapidly gaining importance in Twitter and other micro-blogging communities. Most traditional recommendation systems only rely on content or topology, disregarding the effect of psychological characteristics over the followee selection process. As personality is considered one of the primary factors that influence human behaviour, this study aims at assessing the impact of personality in the accurate prediction of followees. It analyses whether user personality could condition followee selection by combining personality traits with the most common followee recommendation factors.